Drying of Gymnema sylvestre Using Far-Infrared Radiation: Antioxidant Activity and Optimization of Drying Conditions - Abhiram, G.; Briyangari, A.; Eeswaran, R. (MDPI, 2023)
The leaf extracts of Gymnema sylvestre consist of secondary metabolites which are well known for antioxidant activity. This study aimed to measure the drying characteristics of G. sylvestre leaves under far-infrared radiation (FIR) and to optimize the specific energy consumption for drying and antioxidant activity of ethanol-water extract of dried leaves. Fresh leaves were harvested and exposed to combinations of four different temperatures (125, 150, 175 and 200 ◦C) and exposure times (5, 10, 15 and 20 min). Drying kinetics, energy consumption, color changes, total phenolic content (TPC) and antioxidant activities were quantified. Both temperature and drying time have significant (p < 0.05) effects on drying characteristics and antioxidant activity. The equilibrium moisture content was achieved at 200 ◦C and 18 min. The specific energy decreased and total color changes increased with temperature. Under lower temperatures (125 and 150 ◦C), TPC and antioxidant activity increased with exposure time, whereas higher exposure time (20 min) with high temperatures (175 and 200 ◦C) significantly decreased TPC and antioxidant activity. The highest TPC of 30.5 mg TAE/g leaf-fresh weight was achieved at 200 ◦C and 15 min. The optimal drying conditions achieved from the dissimilarity function method were 200 ◦C and 8.4 min.
Keywords: Antioxidant activity; Color changes; Energy consumption; Drying kinetics; Far-infrared; Response surface method